Quantum Yield and Fatty Acid Profile Variations With Nutritional Mode During Microalgae Cultivation - Rohit, M. V.; Venkata Mohan, S. (Frontiers in Bioengineering and Biotechnology, 2018)
Microalgae are gaining commercial interests in the areas food, feed and biofuel sector. They have intrinsic ability to harness energy from sunlight and photosynthetically valorize CO2 into various bio-based products viz., triacylglycerols (TAGs), mono/poly-unsaturated fatty acids (MUFA, PUFA), pigments etc. Microalgae have adapted to grow in various nutritional environments due to their metabolic versatility and resilience. Strategic evaluation of newly isolated strain Chlorella sp. from residential lake was performed by varying the nutritional modes to gain insights into biomass and lipids production. The maximal biomass (3.59 g/l) and lipid yield (670 mg/g DCW) was observed in mixotrophic condition whereas maximum total lipid content (36%) was observed in heterotrophic condition. Autotrophic condition showed higher photosynthetic activity which was well correlated with high fluorescence intensity during pulsed amplitude modulation (PAM) and represented by OJIP, NPQ1 and NPQ2 curves. Good balance of Saturated Fatty Acid (SFA) and unsaturated fatty acids was observed in autotrophic mode, whereas polyunsaturated fatty acids (PUFA) and oleic acid (MUFA) content was enhanced significantly in mixotrophic and heterotrophic conditions.